Implementation of the Ascon authentication algorithm in IoT devices (2023)
This thesis addresses the implementation of Ascon, a lightweight encryption algorithm, on IoT devices. This algorithm emerges in response to the growing need to secure communications between these devices, given their processing and hardware constraints, and it emerged as the winner of the NIST competition on lightweight encryption algorithms due to its robustness and level of protection. The implementation is conducted considering the constraints of the CupCarbon simulator, designed for simulating smart cities and sensor networks. Results obtained in terms of latency from the implementation are analyzed, focusing on response times and resource consumption. Similarly, the implementation of ASCON on Raspberry Pi devices in a context closer to real-world devices is performed. These devices serve as a validation platform to assess the feasibility of the encryption algorithm with limited resources. The analysis of this adaptation highlights its efficiency in IoT devices with constraints on computational capacity. The results obtained from both proposed implementations allow concluding on the viability of ASCON, confirming its ability to secure communications between IoT devices adapted to real-world needs.